2013
DOI: 10.1074/jbc.m112.430223
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Architecture and Functional Analysis of NetB, a Pore-forming Toxin from Clostridium perfringens

Abstract: Background: Clostridium perfringens toxin NetB is a key factor in avian necrotic enteritis.Results: NetB forms heptameric pores structurally similar to Staphylococcus aureus toxins but lacks a phosphocholine binding pocket. NetB activity is enhanced by cholesterol.Conclusion: NetB has distinct binding specificity, and cholesterol may act as a receptor.Significance: The structure of NetB will facilitate development of control measures against necrotic enteritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
135
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(141 citation statements)
references
References 41 publications
6
135
0
Order By: Relevance
“…Like most of these toxins, it is produced as a monomer and presumably oligomerizes on the host cell surface prior to membrane insertion, forming 1.6-to 1.8-nm pores in susceptible chicken leghorn male hepatoma (LMH) cells (11). The structures of both the soluble monomeric form of NetB (133) and a heptameric pore form of NetB (134) have recently been solved, and its structural similarity to S. aureus alpha-hemolysin was confirmed. Although the precise NetB receptor has not been identified, there is evidence for cell specificity, since not all chicken cell lines are susceptible to NetB (11).…”
Section: Plasmid-encoded Toxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like most of these toxins, it is produced as a monomer and presumably oligomerizes on the host cell surface prior to membrane insertion, forming 1.6-to 1.8-nm pores in susceptible chicken leghorn male hepatoma (LMH) cells (11). The structures of both the soluble monomeric form of NetB (133) and a heptameric pore form of NetB (134) have recently been solved, and its structural similarity to S. aureus alpha-hemolysin was confirmed. Although the precise NetB receptor has not been identified, there is evidence for cell specificity, since not all chicken cell lines are susceptible to NetB (11).…”
Section: Plasmid-encoded Toxinsmentioning
confidence: 99%
“…Although the precise NetB receptor has not been identified, there is evidence for cell specificity, since not all chicken cell lines are susceptible to NetB (11). Recent studies have shown that NetB interacts with cholesterol to enhance pore formation (134) and that it formed pores with much higher single-channel conductance than alpha-hemolysin and varied in its ion selectivity, preferring cations over anions (133).…”
Section: Plasmid-encoded Toxinsmentioning
confidence: 99%
“…Using this threading technique, 3 of the 4 amino acid substitutions can be modeled; CPB is slightly larger than NetB (309 versus 293 amino acids, respectively) so the K40N substitution could not be modeled, as it is absent from NetB. This model predicts that the A300V switch occurs on one of 4 loops located near the bottom of the toxin, correlating with the predicted binding or rim domain of NetB (26,30). It appears likely that, based on the homology with NetB and our result, these 4 loops create the binding domain of CPB, although more work is needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the effects of the sequence variations on CPB trypsin sensitivity and cytotoxic activity, CPB was modeled in both the secreted and membrane-active forms by threading the CPB sequence onto the published (29,30) structures of C. perfringens delta and necrotic enteritis beta (NetB) toxins, respectively (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation